2021
DOI: 10.1103/physrevlett.127.236401
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of New van Hove Singularities in the Charge Density Wave State of a Topological Kagome Metal RbV3Sb5

Abstract: Quantum materials with layered kagome structures have drawn considerable attention due to their unique lattice geometry, which gives rise to flat bands co-existing with Dirac-like dispersions. The interplay between strong Coulomb correlations and nontrivial band topology in these systems results in various exotic phenomena. Recently, vanadium-based materials with layered kagome structures are discovered to be topological metals, which exhibit charge density wave (CDW) properties, significant anomalous Hall eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(41 citation statements)
references
References 77 publications
4
36
0
1
Order By: Relevance
“…2a, the DFT band calculation for CsV3Sb5 reveals four bands near EF: an electron-pocket at the Brillouin zone center G (G-band), dxy/dx2-y2 orbital kagome bands with Dirac point at » -0.27 eV and vHS near EF (K1-band), dxz/dyz orbital kagome bands with Dirac point at » -1.08 eV and vHS near EF (K2-band), and additional dxz/dyz orbital kagome bands with opposite parity from the K2-band (K2'-band). All band dispersions have been closely reproduced in previous ARPES studies 19,20,[36][37][38] . Meanwhile, we note that in the experimental geometry used in the present study, only G-, K1-, and K2-bands are visible in the ARPES spectra (see Fig.…”
supporting
confidence: 80%
“…2a, the DFT band calculation for CsV3Sb5 reveals four bands near EF: an electron-pocket at the Brillouin zone center G (G-band), dxy/dx2-y2 orbital kagome bands with Dirac point at » -0.27 eV and vHS near EF (K1-band), dxz/dyz orbital kagome bands with Dirac point at » -1.08 eV and vHS near EF (K2-band), and additional dxz/dyz orbital kagome bands with opposite parity from the K2-band (K2'-band). All band dispersions have been closely reproduced in previous ARPES studies 19,20,[36][37][38] . Meanwhile, we note that in the experimental geometry used in the present study, only G-, K1-, and K2-bands are visible in the ARPES spectra (see Fig.…”
supporting
confidence: 80%
“…Additionally, we are able to pinpoint two distinct CDW gaps in RbV 3 Sb 5 . These gaps are integral to the putative topological state but could be previously observed with surface-sensitive techniques only [12,29]. Our optical study confirms their bulk nature, thus setting a benchmark for the CDW state of AV 3 Sb 5 .…”
Section: Introductionsupporting
confidence: 79%
“…As noted by the arrow, the elastic scattering shows a slight change across the CDW transition. Considering the partial gapping of the Fermi surface [12,29] and the slight change of the carrier density across T CDW , this small change is expected. On the other hand, the backscattering mechanism seems to be unaffected by the CDW.…”
Section: Localization Peakmentioning
confidence: 95%
“…Recently, a family of kagome metals AV 3 Sb 5 (AVS; A = K, Rb, Cs) with a V kagome network [Fig. 1(a)] has emerged [23] as a new platform to study the physics associated with the SP due to its proximity to E F , as revealed by density-functional-theory calculations [23][24][25][26][27][28][29][30][31][32] and angle-resolved photoemission spectroscopy (ARPES) [33][34][35][36][37][38][39]. AVS commonly exhibits superconductivity (T c = 0.9-2.5 K) and charge-density wave (CDW; T CDW = 78-103 K) [27,40,41].…”
mentioning
confidence: 99%